POTENSI KORUPSI DALAM KEBIJAKAN VALIDASI PAJAK PENJUALAN ATAS TANAH DAN ATAU BANGUNAN - Lilik Warsito (UNISSULA, 2016)
Law No. 36 Th. 2008 Income Tax, tax objects including land transfer. A general description that maintaining self-assessment, but in fact a seller who has to pay income tax to get validation from the Tax Office. Discussion: The procedure of payment of income tax, the seller pays the tax-SSP; Then the seller to apply to the Tax Office for validation; Policy validation of payment of income tax can raise the potential for corruption, as stipulated in Law No. 31 Th. 1999 jo. Law No. 20 Th. 2001